REFORMA DO ESTADO E SEUS REFLEXOS NA CONTRATAÇÃO DE MÃO DE OBRA: O CASO DA SUPERINTENDÊNCIA DE ESTUDOS ECONÔMICOS E SOCIAIS DA BAHIA (SEI) - Conceição, Rosangela Ferreira (2012)
This dissertation seeks to demonstrate how different forms of contract labor undertaken by the administrative structure of the SEI, allowed from the administrative reform of 1995, are impacting on the ability of the agency to perform its core activity. Besides, it was attempted to reconstruct the history of the institution by applying semi -structured interviews with people responsible for managing it ever since it was born. It is said that this situation happens, in a more precise way, due to the fact that the State has started to use tools, such as hiring labor, in a larger scale, supported by the managerialist model which has happened in the previously mentioned reform especially outsourcing and other types of hiring, not directly associated with the State, like the REDA, scholarship holders, trainees, commissioned positions to keep control of the expanses of the staff. It is assumed that these hiring approaches, in spite of having allowed the viability of the existence of SEI as an institution, honoring the legal attributions conferred on it by the government, worked as a safety valve to postpone more effective and concrete measures to equate its personnel structural bottleneck. Furthermore, the idea of keeping SEI working is defended and supported also it is imperative that the process of public tender be implemented. It is noteworthy that, if this is not done shortly, such an institution will collapse, and may be terminated as a consequence of lack of personnel to make possible the concretization of the work which is the institution´s responsibility. In order to achieve the goals of this research, it has been decided to undertake an exploratory research, supported documentary and bibliographically. Besides, it was attempted to reconstruct the history of the institution by applying semi -structured interviews with people responsible for managing it ever since it was born.